Review shows that donor milk does not promote the growth and development of preterm infants as well as maternal milk - Hård, Anna‐Lena (Acta Paediatr, 2019)
AIM: This nonsystematic review examined differences in the composition of raw maternal breastmilk and pasteurised donor milk and possible health effects on preterm infants. METHODS: We searched PubMed up to July 2018 for studies published in English that focused on four comparisons as follows: raw maternal milk versus donor milk, human milk before and after Holder pasteurisation, milk from mothers who delivered preterm and at term and milk collected during early and late lactation. We also searched for possible effects of the milk components, as well as the effects of maternal and donor milk on preterm infants’ health. RESULTS: Raw maternal milk contained factors involved in antioxidant and anti‐inflammatory defence, gut microbiome establishment and the maturation of immune defences, food tolerability and metabolism. Many of these factors were reduced or abolished in processed donor milk. Both maternal milk and donor milk have been associated with a reduced incidence of necrotising enterocolitis. High‐dose feeding with maternal milk during the neonatal period reportedly reduced the risk of other morbidities and promoted growth and neurodevelopment. CONCLUSION: Many of the components in raw maternal breastmilk were lacking in pasteurised donor milk, which was inferior in promoting the growth and development of very preterm infants.